The dynamics of place attachment and dependence among the Bugis community in the Oesapa Fishing Village, Kupang in Timor Island (ARTEKS : Jurnal Teknik Arsitektur, 2025)
The issue of place attachment among the Bugis community in the Oesapa Fishing Village, Timor, emerges as a critical topic due to its substantial influence on community identity and sustainability. This study seeks to elucidate the various components that contribute to place attachment and place dependence within migrant communities, a field that remains inadequately understood. Employing a qualitative methodology grounded in a phenomenological framework, data were meticulously gathered through in-depth interviews and participatory observations involving the elder generation of Bugis in Oesapa. The findings indicate that place attachment is multifaceted, encompassing functional elements particularly those related to the marine economy emotional dimensions rooted in familial connections and collective memory, as well as cultural aspects that reflect identity and inherited values. These elements interact in a dynamic manner, effectively reinforcing the community's dependence on their place of residence. In conclusion, the dependence and attachment of the Bugis community to their locality is shaped not solely by physical characteristics but also by profound social and cultural influences. The insights derived from this research have significant implications for the formulation of policies and architectural practices that are attuned to the local cultural context.
Keywords: Bugis ethnic; Cultural identity; Oesapa fishing village; Place attachment; Place dependence; Qualitative research